Phospholipids of the Thiobacilli - Barridge, Judith K. (1968)
Phosphatidyl glycerol, disphosphatidyl glycerol, and phosphatidyl ethanolamine were found in all of the Thiobacillus species studied. T. thioparus possessed only these phospholipids. T. intermedius, T. neapolitanus, and T. thiooxidans contained phosphatidyl-N-monomethylethanolamine, and T. novellus lipids contained phosphatidyl-N-monomethylethanolamine, phosphatidyl-N-N-dimethylethanolamine, and phosphatidyl choline, in addition to the three phospholipids common to all of the thiobacilli. Methionine was found to act as a methyl donor in the biosynthesis of the methylated forms of phosphatidyl ethanolamine. Phosphatidyl inositol was not detected in any of the organisms. Changing the nutrient medium did not result in a qualitative change in the phospholipid spectrum of the cultures.